Confinement effects in irradiation of nanocrystalline diamond - Valencia, Felipe (2015)
Swift heavy ion irradiation does not generate amorphous tracks in diamond, contrary to what happens in graphite or in diamond-like carbon. Since nanocrystalline diamond is of interest for several technological applications we investigate the reason for this difference, by means of large scale atomistic simulations of ion tracks in nanocrystalline diamond, using a thermal spike model, with up to 2.5 million atoms, and grain sizes in the range 5-10 nm. We conclude that tracking can be achieved under these conditions, when it is absent in single crystal diamond: for 5 nm samples the tracking threshold is below 15 keV/nm. Point defects are observed below this threshold. As the energy loss increases the track region becomes amorphous, and graphitic-like, with predominant sp2 hybridization. This higher sensitivity to irradiation can be related to a very large decrease in thermal conductivity of nanocrystalline diamond, due to grain boundary confinement of the heat spike which enhances localized heating of the lattice.